Social impact of international legal regulation of environmental safety during armed conflicts - Krasnova, Juliia; Ladychenko, Viktor; Makarenko, Oleksandr; Kidalov, Serhii; Yankovskyi, Stanislav (Interacción y Perspectiva, 2023)
The purpose of the article is to analyze international legal documents regarding the possibility of their application for the purpose of insuring environmental safety and social safety, mainly human life and health, during armed conflict. To achieve this purpose, general and special scientific research methods were used, in particular historical-legal, dialectical, systematic, comparative legal methods. War is the most terrible phenomenon in human relations, which has huge social influence. The reasons for its occurrence are quite diverse - it is a reaction to insults, and the desire to rule over other peoples, the desire to take away valuable natural resources that another country is rich in, etc. But whatever the cause of the war, it does not justify the devastating consequences it brings - the killing of a large number of people, the destruction of property, infrastructure, economies and the environment of countries. However, knowing and understanding all this, society does not draw conclusions, but creates new and new conflicts. Insuring environmental safety during armed conflicts have social impact through protection of human health and human life. The main provisions and results of the article are formulated on the basis of the analysis of the norms of international and national legislation.